THE EFFECTIVENESS OF POE (PREDICT-OBSERVE-EXPLAIN) BASED TEACHING STRATEGY IN IMPROVING STUDENTSâ CONCEPTUAL UNDERSTANDIN - ANARKY, VIOLANTI; SYUHENDRI, SYUHENDRI; AKHSAN, HAMDI (Sriwijaya University Learning and Education International Conference, 2016)
The objective of this research is to determine the effectiveness of POE (Predict-Observe-Explain) based teaching strategy in improving studentsâ conceptual understanding on Heat and temperature in SMAN 09 Palembang. The research was conducted on even semester in Academic Year 2015/2016. The research used the quasi experimental method with non-equivalent control group design. The sample comprising of 80 students was selected by using purposive technique sampling. The learning process in the experimental group used POE (Predict-Observe-Explain) based teaching strategy and in the control group used conventional one. The instruments used are the Thermal Concept Evaluation (TCE) consisting of 20 multiple choice questions to measure studentâs conceptual understanding and observation sheet to observe the studentsâ activities during the lesson. Based on the data analysis using Z-test on significance (Î±) = 0.05, it was found that Zcount= 4.16 and Ztabel= 1.645 showed Zcount > Ztabel. The result was Ho was rejected and Ha was accepted. The conclusion is the POE (Predict-Observe-Explain) based teaching strategy was effective to improve learnersâ conceptual understanding on Heat and temperature topics.